Eksistensi Lembaga Bantuan Hukum Dan Kesadaran Hukum Masyarakat - Farid, Achmad Miftah (CV. Strata Persada Academia, 2023)
The existence of an advocacy institution is crucial as an independent institution that is outside the government. Law becomes an essential entity in protecting human rights. This study aims to examine the existence of legal aid institutions in Indonesia and their implications for the legal awareness of the Indonesian people in the study of the sociology of law. This research is socio-legal research with a statutory regulation approach. This study found that the existence of legal aid institutions in Indonesia has been recognized by Law Number 16 of 2011 concerning Legal Aid and Law Number 18 of 2003 concerning Advocates. Because of this legal umbrella, it is hoped that all people can access justice through legal aid institutions to achieve justice for all levels of society without exception.